THE IMPACT OF MIGRATION PROCESSES ON THE INTEGRATION OF YOUNG PEOPLE INTO THE LABOR MARKET - Safarov Akbar Isakulovich (Western European Studies, 2025)
This article examines the influence of migration processes on youth integration into the labor market. Migration, both internal and international, has become a significant factor shaping the professional opportunities and career development of young people. The study analyzes how migration affects employment prospects, skill acquisition, and economic participation among youth. It highlights the challenges migrants face, such as social adaptation, discrimination, and access to resources, while also discussing potential benefits, including exposure to diverse work environments and skill enhancement. The article employs qualitative and quantitative data to assess the overall impact of migration on youth employment patterns and offers recommendations for policies that support effective labor market integration for migrant youth
Keywords: Migration; Youth Employment; Labor Market Integration